Physical activity and sedentary behavior among Chinese children aged 6–17 years: a cross-sectional analysis of 2010–2012 China National Nutrition and health survey - Chao Song; Weiyan Gong; Caicui Ding; Fan Yuan; Yan Zhang; Ganyu Feng; Zheng Chen; Ailing Liu (BMC Public Health, 2019)
Abstract Background Patterns of physical activity (PA) and sedentary behavior have important implications for child health. The purpose of the study was to describe the PA and sedentary behavior among Chinese children. Methods The study analyzed the PA and sedentary behavior status of 38,744 Chinese children aged 6–17 years, based on the data from China National Nutrition and Health Survey (CNNHS) in 2010–2012. Results Chinese children spent 61.6 min/d on school-time PA and the proportion with 60 min and over on school-time PA was 52.5%. The average transportation time was 38.5 min/d and the main mode for children was walking (50.9%), followed by taking private vehicles (19.4%), taking public transportation (16.4%) and cycling (13.3%). Approximately 70% Chinese children did domestic PA and they spent 17.2 min/d on it. Children spent 2.9 h per day on leisure-time sedentary behaviors and 85.8% of them engaged in sedentary behaviors longer than 2 h/d. The proportion of children participating in leisure-time PA was 35.4%and they performed moderate-to-vigorous PA on 3.4 days per week with average 44.9 min per day. Boys were more active in school-time PA, leisure-time PA and transportation, while girls spent more time on domestic PA and homework. More older children took active transportation and spent more time on domestic PA, leisure-time PA and sedentary behaviors compared with younger children. Children in urban area were more likely to take inactive transportation and participate in leisure-time PA, spent less time on domestic PA while more time on sedentary behaviors compared with their counterpart. Conclusions Chinese children performed little physical activity and spent long time engaging in sedentary behaviors. Their physical activity and sedentary behaviors varied by gender, age and area.